Analysis of Customer Loyalty and Satisfaction Using Structural Equation Modeling (SEM) Approach - Adinda Permata Sari; Christian Harito (Postgraduate, University of Mataram, 2025)
This study aims to analyze the factors influencing customer satisfaction and loyalty at PT. PLN (Persero) ULP Tanjung Morawa using the Structural Equation Modeling (SEM) approach. A quantitative method was applied by distributing structured questionnaires to 150 customers selected through purposive sampling. The analysis was conducted using SmartPLS version 3.0. The results indicate that customer satisfaction has a significant positive effect on customer loyalty. Furthermore, perceived service quality and perceived value significantly influence customer satisfaction, while trust has a strong and significant effect on customer commitment. However, trust does not directly affect customer loyalty. These findings suggest that improving service quality and building trust are essential strategies to enhance customer satisfaction and commitment, which in turn foster customer loyalty. The study provides practical insights for PT. PLN to refine its customer relationship strategies in response to competitive service demands.